Estimating Investment Project Revenue and Expenditure in Telecommunication Sector - P. D. Sysoev (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article studies the process of estimating investment project revenue and expenditure in telecommunication sector, illustrated by the public company ‘MTS’: key technologies of data transfer, their correlation with frequencies, structure of expenses on network building, approaches to estimation of project revenue. The author identified types of investment projects in view of different approaches to their evaluation: qualitative projects, which do not cause direct rise in profits and quantitative ones, whose estimation is possible by present value of cash flows. Advantages and drawbacks of the current approach to estimation of ‘MTS’ projects were formulated. The article shows technical and economic indices that can impact project efficiency and seriously change its recoupment. The author proposes to include costs of the network development not only of the access level but also of the level of aggregation and network core; to extend the horizon of planning network quality indices for the whole period of the project; to take into account costs of the future extension of network capacity during project implementation; to carry out modernization of the equipment in case of its technical support termination and output of components. With regard to discontinuity of network modernization steps it is necessary to account for the effect of growing quality of services above the target indicators.